Peran Profesi Akuntan dalam Meningkatkan Ketahanan Keuangan di Era Vuca - Zahra, Bilqist Nabila; Yuhertiana, Indrawati (Studi Akuntansi dan Keuangan Indonesia, 2025)
This study aims to analyze the development of publications, trends, and dynamics related to the topic of the Accounting Profession and Financial Resilience in the VUCA Era (Volatility, Uncertainty, Complexity, Ambiguity) from 2020 to 2024, as well as to identify scientific articles with the highest number of publications on this topic. The data was collected using the Publish or Perish application with Google Scholar as the database. The implemented criteria included article titles, abstracts, and keywords within the time frame of 2020–2024. The search process resulted in 200 articles, which were further analyzed using VOSviewer software, yielding 85 articles relevant to the topic of the Accounting Profession and Financial Resilience in the VUCA Era. Subsequently, through variable selection in VOSviewer, 24 variables were identified as being associated with the accounting profession and its role in financial resilience in the VUCA era.